2020
DOI: 10.1007/s11695-020-05133-8
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial Comparing the Impact of a Low-Calorie Ketogenic vs a Standard Low-Calorie Diet on Fat-Free Mass in Patients Receiving an Elipse™ Intragastric Balloon Treatment

Abstract: Background The Elipse™ intragastric balloon (EIGB) is a new swallowable balloon for weight loss (WL). Preserving metabolically active fat-free mass (FFM) and resting metabolic rate (RMR) during WL are crucial to maximize fat mass (FM) loss. After EIGB placement, a standard low-calorie diet (LCD) is generally prescribed. A low-calorie ketogenic diet (LCKD) has proven to be safe and effective in reducing FM while preserving FFM and RMR. Objective To prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Furthermore, body weight (BW) reduction is associated with improvements in OSAS, with a 10% reduction in BW predicting an approximate 26-32% change in the AHI score [9]. An accurate preoperative multidisciplinary assessment of bariatric patients plays an important role in improving performance status, surgical outcome, and WL [10][11][12][13][14][15][16][17]. Previous studies have reported that a low-calorie ketogenic diet (LCKD) is safe and effective in reducing BW and liver volume in patients scheduled for BS, resulting in a reduction of intraoperative complications and operating time [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, body weight (BW) reduction is associated with improvements in OSAS, with a 10% reduction in BW predicting an approximate 26-32% change in the AHI score [9]. An accurate preoperative multidisciplinary assessment of bariatric patients plays an important role in improving performance status, surgical outcome, and WL [10][11][12][13][14][15][16][17]. Previous studies have reported that a low-calorie ketogenic diet (LCKD) is safe and effective in reducing BW and liver volume in patients scheduled for BS, resulting in a reduction of intraoperative complications and operating time [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fat mass decreased more significantly with LCKD compared to LCD (41.6 vs. 33.1%, p = 0.0606). The authors concluded that, based on their findings, they were able to support the hypothesis that LCKD is associated with an increased fat mass loss while reducing the fat free mass loss and the resting metabolic rate [116]. In addition, in another study, Schiavo et al were able to show in a pilot, prospective, randomized multicentre comparative study that LCKD associated with continuous positive airway pressure was able to alleviate OSAS in patients with obesity scheduled for bariatric/metabolic surgery [117].…”
Section: Breakfastmentioning
confidence: 94%
“…All subjects obtained a significant reduction in body weight (males 10.3%, p < 0.001 and females 8.2%, p < 0.001) and in left hepatic lobe volume (−19.8%; 503 ± 61 cm 3 vs. 627 ± 85 cm 3 , p < 0.001) [50]. Furthermore, Schiavo et al, with the aim to prospectively compare the effects on weight loss, fat mass, fat free mass, and resting metabolic rate in two groups of patients with obesity scheduled for BS and who were randomized to two different diets (LCKD diet vs. LCD) after intragastric balloon placement, showed that the LCKD group displayed a significantly lower decrease in fat free mass and resting metabolic rate when compared with the LCD group (3.55 vs. 14.3%, p < 0.001; 9.79 vs. 11.4%, p < 0.001, respectively) [116]. Moreover, fat mass decreased more significantly with LCKD compared to LCD (41.6 vs. 33.1%, p = 0.0606).…”
Section: Breakfastmentioning
confidence: 99%
“…Importantly, KD-induced weight loss is generally higher than that achieved with an isocaloric non-ketogenic control diet ( Table 2 ), as shown in several populations including hyperinsulinemic ( 48 ) overweight females ( 75 ), overweight/obese subjects ( 34 , 72 74 , 76 , 77 ) and in morbidly obese subjects candidate to bariatric surgery ( 79 ). In addition, weight reduction following a KD is demonstrated to be accompanied by favourable changes in body composition with a higher decrease in waist circumference ( 48 , 75 , 76 ) and fat mass loss ( 72 , 74 ), also in subjects who underwent gastric balloon procedure ( 80 ), vs control diets.…”
Section: Effects Of Ketogenic Diets In Obese Subjectsmentioning
confidence: 99%